2009
DOI: 10.1073/pnas.0811922106
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal protein solubility distribution revealed by an aggregation analysis of the entire ensemble of Escherichia coli proteins

Abstract: Protein folding often competes with intermolecular aggregation, which in most cases irreversibly impairs protein function, as exemplified by the formation of inclusion bodies. Although it has been empirically determined that some proteins tend to aggregate, the relationship between the protein aggregation propensities and the primary sequences remains poorly understood. Here, we individually synthesized the entire ensemble of Escherichia coli proteins by using an in vitro reconstituted translation system and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
428
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 280 publications
(460 citation statements)
references
References 42 publications
26
428
1
5
Order By: Relevance
“…Aggregation Propensities of GroE-dependent UuMetK Mutants-Almost all GroE obligate substrates show strong aggregation propensities, according to the global aggregation analysis under the chaperone-free conditions (4,13). Thus, we investigated the in vitro aggregation properties of representative UuMetK mutants, K215F and K215F/I216F, which were converted to GroE-dependent substrates, by a conventional light scattering assay.…”
Section: Systematic Chimeric Analysis Between Ecmetk and Uumetk-mentioning
confidence: 99%
See 2 more Smart Citations
“…Aggregation Propensities of GroE-dependent UuMetK Mutants-Almost all GroE obligate substrates show strong aggregation propensities, according to the global aggregation analysis under the chaperone-free conditions (4,13). Thus, we investigated the in vitro aggregation properties of representative UuMetK mutants, K215F and K215F/I216F, which were converted to GroE-dependent substrates, by a conventional light scattering assay.…”
Section: Systematic Chimeric Analysis Between Ecmetk and Uumetk-mentioning
confidence: 99%
“…However, folding often competes with a side reaction, intermolecular aggregate formation, which usually impairs the functions of proteins (2,3). Indeed, a global aggregation analysis of thousands of Escherichia coli proteins, using a reconstituted cellfree translation system, revealed that ϳ30% of proteins are aggregation-prone (4). The cellular milieu, where proteins and other molecules exist in highly crowded conditions, further increases the risk of aggregate formation (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithms used to map surface properties (electrostatic potential and hydrophobicity) are based on a protein solubility database of E. coli proteins 51. This study has shown that the algorithm can be implemented in the context of recombinant protein production in a mammalian expression system.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence and structural predictions of protein solubility were obtained from computational work based on comparison with the solubility database of all E. coli proteins (eSOL) which contains the solubility distribution of 3173 E. coli proteins produced in a cell‐free expression system 51. It was found that the experimental solubility values (eSOL) were, on average, inversely correlated with size of calculated largest positive electrostatic potential patch 37.…”
Section: Methodsmentioning
confidence: 99%